Cumulative environmental exposures and metabolic syndrome: A study of heavy metals and volatile organic compounds - Brooke Scardino; Destyn Dicharry; Akshat Agrawal; Diensn Xing; Md. Mostafizur Rahman Bhuiyan; Md. Shenuarin Bhuiyan; Oren Rom; Steven A. Conrad; John A. Vanchiere; A. Wayne Orr; Christopher G. Kevil; Mohammad Alfrad Nobel Bhuiyan (Ecotoxicology and Environmental Safety)
Background: Metabolic Syndrome (MetS), a condition affecting over one-third of the U.S. population, heightens the risk of cardiovascular disease, Type 2 diabetes, and premature mortality. While individual links between heavy metals (HM), volatile organic compounds (VOC), and MetS have been established, the impact when these environmental toxins are combined remains unclear and unexplored. This study investigates how simultaneous exposure to HMs and VOCs influences the risk of MetS. Methods: Weighted Quantile Sum regression and Bayesian kernel Machine Regression were performed on data from 6603 participants in the National Health and Nutrition Examination Survey (2011–2020) to determine the impact of HMs and VOCs detected in urine on MetS. Further analyses were performed for individuals placed in subgroups based on age, sex, race/ethnicity, and monthly poverty level index. Results: The analyses reveal that combined exposure to HMs and VOCs is associated with an increased risk of MetS; in particular, exposure to cadmium, tin, N-acetyl-S-(N-methyl carbamoyl)-L-cysteine, and N-acetyl-S-(2-carboxyethyl)-L-cysteine significantly elevates the risk of developing MetS. Younger adults (18–50 years), men, Hispanics and non-Hispanic whites, and those with a monthly poverty index > 1.3 (higher socioeconomic status) emerged as the most vulnerable groups. Conclusion: These findings emphasize an urgent need to address and tackle the cumulative impact of environmental toxins through a shift in public health efforts to go beyond investigating isolated exposures to address real-world chemical exposures. By understanding these cumulative risks, we can begin to mitigate them and pave the way for more effective interventions, especially for at-risk populations.